OPTIMALISASI PENGAWASAN PENYIDIKAN DALAM MENINGKATKAN KINERJA SATUAN RESKRIM POLRES TEMANGGUNG GUNA TERWUJUDNYA GAKKUM YANG PRESISI - GHOZI FALAH (Advances in Police Science Research Journal, 2022)
ABSTRACT OPTIMIZING INVESTIGATION SUPERVISION IN IMPROVING THE PERFORMANCE OF THE TEMANGGUNG POLRES RESCRIME UNIT FOR THE ESTABLISHMENT OF PRECISION GAKKUM GHOZI ALFALAH, 18.052, ghozi.falah@gmail.com Focus study in Duty end this is optimization supervision investigation in Upgrade performance Unit Reskrim police station Temanggung To use realization PRECISION Gakkum . Focus study this looked at important done because 5 years final solution act criminal not optimal. By because that , Unit Crime police station Temanggung try optimizing supervision investigation so that its implementation in accordance with Perkabareskrim Number 4 of 2014 concerning Supervision Investigation . Study this aim for : (1) Describe implementation of monitoring system investigation in Upgrade crime sat performance police station Temanggung To use realization PRECISION Gakkum , (2) found and describe effort optimization supervision investigation in Upgrade crime sat performance police station Temanggung To use realization PRECISION Gakkum . On literature conceptual for analyze the above problems , some theory used in study this , namely ; theory Management , theory FFA analysis , and theory element Management . Whereas the concept used as base theory , namely ; draft supervision investigation , concept Performance , concept PRECISION Gakkum . In study this used method qualitative with descriptive analysis for processing data and study field ( field research ) use get data online direct with participant observation . Primary data sources and secondary , using data triangulation for get data validity . Results findings During study this namely (1) Supervision investigation still not yet maximum , implementation supervision investigation not yet completely customized with Perkabareskrim Number 4 of 2014 concerning Supervision Investigations , such as no made plan activity and not yet made report results implementation activity supervision investigation . (2) Effort optimization supervision investigation Satreskrim in supervision investigation hampered because limitations personnel wasidik and not yet evenly ability investigator . Conclusion in Duty end this , (1) Supervision investigation by Satreskrim police station Temanggung still not yet maximum , implementation supervision investigation this should adapt with Perkabareskrim Number 4 of 2014. (2) Efforts optimization supervision investigation in Upgrade performance Satreskrim not yet done with good because lack of coordination with investigator Satreskrim and implementation supervision investigation which only character flow without existence plan activity